2018
DOI: 10.1021/acs.jpcc.8b04996
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Impact on the Crystal Structure, Optical, and Transport Properties in Layered Oxychalcogenides BiCuChO (Ch = S, Se)

Abstract: The layered oxychalcogenides BiCuChO (Ch = S, Se, Te) represent a unique family of two-dimensional semiconductors with extraordinary optoelectronic and thermoelectric properties. Chemical strategies such as elemental doping have been used to modify their crystal structures and electronic configurations for better photocatalytic performances. Herein, we report the pressure impact on the crystalline and electronic band structures of BiCuChO (Ch = S, Se) with in situ synchrotron X-ray diffraction, Raman spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
7
15
3
Order By: Relevance
“…Figure 2 shows a comparison of the experimental Raman spectra of BiCuSeO and BiCuSO recorded at room temperature between 30 and 500 cm −1 . These spectra are in good agreement with the spectra at ambient conditions in the recent work of Zhang et al 28 In the case of BiCuSeO, four strong lines can be observed located at 55, 85, 147, and 177 cm −1 . They correspond to the four Raman M1−M4 modes found by Zhang et al 28 The two tiny features at 102 and 113 cm −1 are not significant because their magnitudes are comparable to the background noise.…”
Section: Zone-center Phonon Modessupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 2 shows a comparison of the experimental Raman spectra of BiCuSeO and BiCuSO recorded at room temperature between 30 and 500 cm −1 . These spectra are in good agreement with the spectra at ambient conditions in the recent work of Zhang et al 28 In the case of BiCuSeO, four strong lines can be observed located at 55, 85, 147, and 177 cm −1 . They correspond to the four Raman M1−M4 modes found by Zhang et al 28 The two tiny features at 102 and 113 cm −1 are not significant because their magnitudes are comparable to the background noise.…”
Section: Zone-center Phonon Modessupporting
confidence: 91%
“…20 To discriminate between these different possibilities and understand the origin of the intrinsically low thermal conductivity in BiCuSeO and related compounds, the study of the experimental lattice dynamics in BiCuChO compounds is of fundamental interest. However, to our knowledge, there is only one infrared spectroscopic study of the lattice vibrations of BiCuSeO 27 and one very recent Raman spectroscopic study of the lattice vibrations of both compounds; 28 both have been reported at room temperature. In this Raman study, the assignment of the Raman modes of BiCuSeO is made following the calculations of Saha, 14 whereas that of BiCuSO was made without the support of any theoretical study.…”
Section: Introductionmentioning
confidence: 99%
“…And esterification of acetic acid separately with n-butanol and 2ethylbutanol takes place to produce butyl acetate and 2-ethylbutyl acetate (reactions 17 and 18). [21,22]…”
Section: Ethanol Guerbet Condensation Reaction Networkmentioning
confidence: 99%
“…A different way to use QDs in an electrochemical DNA sensor has been considered by Zhang et al. for the detection of specific DNA sequences of bladder cancer cells. In this work, QDs are not used as signal tags, but as modifiers on the GCE transducer surface.…”
Section: Metallic Qds As Signal Amplifiers In the Detection Of Clinimentioning
confidence: 99%